Ninth International Symposium "Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques" Livorno (Italy) 14th-16th June 2022 - Bonora, Laura; Carboni, Donatella; De Vincenzi, Matteo; Matteucci, Giorgio (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The ninth International Symposium Monitoring of Mediterranean Coastal Areas: Problems and Measurements Techniques was organized by CNR-IBE in collaboration with Italian Society of Silviculture and Forest Ecology, and Natural History Museum of the Mediterranean and under the patronage of University of Florence, Accademia dei Lincei, Accademia dei Georgofili, Tuscany Region, The North Tyrrhenian Sea Ports System Authority, Livorno Municipality and Livorno Province. In the Symposium Scholars had illustrated their activities and exchanged innovative proposals, with common aims to promote actions to preserve coastal marine environment. Despite the COVID 19 pandemic, the success of this edition is attested by the 170 contributions selected by the Scientific Committee from among those received. Participation involved all the thematic lines envisaged by the sessions, involving many countries of the Mediterranean Sea. A big endeavor for a costal environment of paramount importance but threatened by global changes. The importance of this Proceedings is attested by the fact that this volume is the first issue of a new FUP Series.